Guided Discovery Learning Model Using Concept Map Strategy to Improve Students Metacognition and Critical Thinking Skills - Muhali Muhali; Roniati Sukaisih (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to improve students' metacognition and critical thinking skills in learning physics through the implementation of the guided discovery learning model with a concept map strategy. This research is a classroom action research, with stages: (1) planning, (2) implementation, (3) observation and evaluation, and (4) reflection. The subjects of this study were 30 students of class XI IPA MAN 3 Central Lombok. The research instrument consisted of metacognition skill assessment sheets and critical thinking tests, which were declared valid and reliable. Data analysis was carried out in a quantitative descriptive manner. The results of this study are: (1) students' metacognition skills experienced an increase in scores in the high category of 33.33% (cycle I), 80.00% (cycle II), and 86.67% (cycle III) ; (2) students' critical thinking skills also experienced an increase in scores in the high and very high categories with a percentage of 63.33% (cycle I), 76.66% (cycle II), and 86.67% (cycle III). thus, the implementation of the guided discovery learning model with a concept map strategy can improve students' metacognition and critical thinking skills in learning physics